Bovine fasciolisis in São Paulo state, Brazil - Mendes, Tiago Manuel Fernandes; Filho, David Vilas Boas; Bataglioli, Acácio Santo; do Prado, Angelo Pires; Madi, Rubens Riscala; Ueta, Marlene Tiduko; Pinto, Mara Cristina [UNESP]; Allegretti, Silmara Marques (Elsevier, 2019)
Fasciolosis is a zoonotic disease with a worldwide distribution caused by Fasciola hepatica, which leads to severe economic losses in cattle such as reducing meat and milk production, livers condemnation, growth retardation and increase in mortality. From October 2008 to April 2011, condemned bovine livers in slaughterhouses of different municipalities from São Paulo state, Brazil were evaluated for the presence of Fasciola hepatica. Out of 20,635 analyzed livers, 1422 were infected with F. hepatica. These cattle came from 33 municipalities, out of which 16 showed infected animals and where 7 municipalities did not show statistical difference between each month throughout the year: Tuiuti – 276/1408 (19,6%), Atibaia – 44/257 (17,1%), Joanópolis – 116/738 (15,7%), Bragança Paulista – 318/2316 (13,3%), Piracaia – 182/1442 (12,6%), Santo Antonio de Posse – 118/1005 (11,7%), Amparo 131/2003 (6,5%). The other nine municipalities, Monte Alegre do Sul, Descalvado, Campinas, Morungaba, Pedreira, Socorro, Munhoz, Jaguariúna and Itatiba showed a positive percentage varying from 5.08% to 1.46%. Our results demonstrated the presence of F. hepatica in this region was higher than official data, bringing the need for control measures. There is also an apparent increase in fasciolosis two to three months after low to medium precipitation, however high precipitation causes a decrease in fasciolosis prevalence.
Keywords: Bovines; Epidemiology; Fasciola hepatica; Fasciolosis